Validation of the Gestational Diabetes Mellitus Knowledge Questionnaire (GDMKQ) among Filipino Patients in a Tertiary Medical Center - Go, Hanah; Gan, Florence Rochelle (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objectives. Gestational diabetes mellitus (GDM) is a common pregnancy complication with adverse fetal and maternal outcomes. Currently, there are only a few validated tools available that address knowledge in GDM. Recognition of the inconsistencies will provide for an effective learning program to achieve optimal results. This study aimed at validating the “Gestational Diabetes Mellitus Knowledge Questionnaire” (GDMKQ). Methodology. A cross-sectional validation study on GDMKQ among 51 GDM patients aged at least 18 years was conducted in the outpatient clinics of a tertiary hospital. Excluded were those with pre-existing diabetes. The questionnaire was submitted for peer review for translation to Filipino and back-translation. Concurrent validity, internal consistency and test-retest reliability of the questionnaire were undertaken as part of the validation process. Descriptive analysis was used for data elaboration by using SPSS v23. Results. The Filipino version of GDMKQ demonstrated sensible content and face validity. As measured, respondents obtained higher total and domain scores with better knowledge levels of GDM compared to its English version. An overall adequate knowledge was observed among those married and college subgroup as compared to single women and those with secondary level of education. The reliability of the questionnaire was calculated at 0.632 using the Kuder-Richardson 20. The test-retest scores using the Filipino-translated questionnaire has a Pearson correlation coefficient of 0.853 with moderate to good level of agreement with each other, and Cohen’s kappa of 0.564 with an intra-class correlation coefficient of 0.828. Conclusion. The Filipino-translated version of GDMKQ is a valid screening tool that assesses a patient’s knowledge of gestational diabetes. Identifying the level of their understanding will enable clinicians to develop an individualized, effective learning program to improve pregnancy outcomes.